IMPACT OF SUPPORTIVE LEADERSHIP, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND WORK ENGAGEMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION IN A LOGISTICS COMPANY - Srihandayani, Yayuk; Barry, Rinto Rain (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study examines the influence of supportive leadership, organizational citizenship behavior (OCB), and work engagement on employee performance and job satisfaction, as well as the mediating role of job satisfaction. It adopts a quantitative approach using purposive sampling. Data was collected through questionnaires from 113 respondents and analyzed using PLS-SEM with the SMART PLS application. The findings indicate that supportive leadership does not have a significant effect on employee performance. However, OCB shows a significant positive influence on performance. Meanwhile, work engagement does not have a significant effect on employee performance. On the other hand, all three variables—supportive leadership, OCB, and work engagement—have a significant positive effect on job satisfaction. Furthermore, job satisfaction significantly enhances employee performance. Another key finding is that job satisfaction serves as a significant mediator between supportive leadership and employee performance. In addition, it also significantly mediates the effects of OCB and work engagement on performance. Therefore, job satisfaction is a crucial factor in improving employee performance through various behavioral and organizational support aspects. These findings highlight the importance of creating a supportive work environment and encouraging positive behaviors in the workplace.